2015
DOI: 10.12693/aphyspola.127.1706
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Study of the Magnetic Properties of (Fe30Co70)100-xZnxNanowire Arrays

Abstract: (Fe30Co70)100−xZnx (0 ≤ x ≤ 10) nanowires with diameters of ≈37 nm have been fabricated by AC electrodeposition into pores of anodized aluminum oxide (AAO) templates. The Fe30Co70 and Zn contents of the nanowires have been adjusted by varying the ratio of Fe30Co70 and Zn ion concentrations in the electrolyte. The eect of the Zn content and annealing on the magnetic properties (e.g., coercivity and squareness) of nanowires arrays have been investigated using X-ray diraction, scanning electron microscopy, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several authors have reported in the literature the use of X-ray diffraction in the BraggÀBrentano mode to study the crystalline structure of the FeCo Nw arrays growing in alumina templates and using aluminum as the substrate with lengths smaller than 10 μm. [26,28,31,35,46,52,53,[64][65][66] However, other authors reported that when XRD measurements were done in the BraggÀBrentano mode for Nws shorter than 10 μm after removal of the aluminum substrate and replaced with a metallic film (Au and/or Cu) as work electrode, these films deposited on the backside of the nanoporous alumina template were detected in the diffractograms. [17,49,67,68] For these reasons, we consider that the structural analysis of FeCo Nw arrays in alumina templates on aluminum substrates with lengths shorter than 10 μm must be done in the grazing-incidence X-ray diffraction (GIXRD) mode instead of the XRD BraggÀBrentano mode.…”
Section: Morphology Composition and Structure Of The Fe 67 Co 33 Nwsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported in the literature the use of X-ray diffraction in the BraggÀBrentano mode to study the crystalline structure of the FeCo Nw arrays growing in alumina templates and using aluminum as the substrate with lengths smaller than 10 μm. [26,28,31,35,46,52,53,[64][65][66] However, other authors reported that when XRD measurements were done in the BraggÀBrentano mode for Nws shorter than 10 μm after removal of the aluminum substrate and replaced with a metallic film (Au and/or Cu) as work electrode, these films deposited on the backside of the nanoporous alumina template were detected in the diffractograms. [17,49,67,68] For these reasons, we consider that the structural analysis of FeCo Nw arrays in alumina templates on aluminum substrates with lengths shorter than 10 μm must be done in the grazing-incidence X-ray diffraction (GIXRD) mode instead of the XRD BraggÀBrentano mode.…”
Section: Morphology Composition and Structure Of The Fe 67 Co 33 Nwsmentioning
confidence: 99%
“…This result suggests that the electrodeposited Nws are stressed [67] due to the rapid deposition of Fe 2þ and Co 2þ into the nanopores. [31,34] Moreover, the confined template-assisted growth forces to lodge atoms in the nanocavities and yields structural defects. [72] The granular structure of the Nws was analyzed with TEM images, as shown in Figure 5b.…”
Section: Morphology Composition and Structure Of The Fe 67 Co 33 Nwsmentioning
confidence: 99%
See 1 more Smart Citation